PUBLIC PERCEPTION ON IMPORTANCE OF SCREENING FOR HIV IN VOLUNTARY COUNSELLING AND TESTING (VCT) (Journal of Pharmaceutical Negative Results, 2022)
The aim of this study was to obtain public perception on importance of screening in VCT and possible barriers. A validated questionnaire was utilized for this study whereby three variables of the study (patient perception, importance of screening and voluntary counseling and testing) were measured using a 5-point Likert scale. 500 questionnaires were distributed to target respondents of registered clinics in Malaysia. The data were analyzed utilizing SPSS software version 21.0. There were 402 completed and usable responses received, which represented an 80.4% response rate. This study showed both patient attitudes and importance of screening a direct relationship with voluntary counseling. Health information utilizing simple language and attractive diagrams were important. Similarly, patient attitudes played a major role in generating interest in health information in private clinics. Perceived Barriers towards HIV screening in VCT canters (PBV) and the Intention to screen at VCT canters (ITSV) are important among patients in private general practitioner clinics as well as general public.